THE EFECT OF PROGRESSIVE MUSCLE RELAXATION ON REDUCING BLOOD PRESSURE IN HYPERTENSION PATIENTS IN BANTERAN VILLAGE: CASE REPORT - Nila Azizatul Mudawammah; Nuriya Nuriya; Made Sumarwati (International Journal of Biomedical Nursing Review, 2025)
Background : Hypertension is a condition when systolic blood pressure is ≥140 mmHg or diastolic blood pressure is ≥90 mmHg. One of the signs and symptoms of hypertension is a stiff neck or neck pain. Non-pharmacological management of hypertension can be done with Progressive Muscle Relaxation (ROP). Purposes : To identify the effect of implementing progressive muscle relaxation in reducing blood pressure in hypertension sufferers in Banteran Village. Methodology : The method used in this final scientific work is a case report in the form of applying Evidence Based Practice (EBP) Progressive Muscle Relaxation (ROP) to Mrs. S once for six days and the patient continues to use pharmacological therapy to lower blood pressure. Results: Implementation results show that ROP has an effect on reducing blood pressure in Mrs. S. Blood pressure on the first day before ROP was 165/95 mmHg, after ROP was 144/88 mmHg. On the sixth day, blood pressure before ROP was 138/79 mmHg, then after ROP it became 125/77 mmHg. Conclusion : The ROP given to Mrs. S has a positive influence where the patient's blood pressure decreases every day.